THE IMPLEMENTATION OF UNIFORM STANDARDS OF REPORTING FOR NATIONAL VOLUNTARY AGENCIES. - Boutell, W. S. (The Accounting Review, 1962)
Abstract This article focuses on the implementation of uniform standards of reporting for national voluntary agencies. The purpose of this article is to point out some of the pitfalls that may be encountered in the development and implementation of uniform standards of reporting in voluntary agencies. Since the lack of adequate funds for accounting data is very apparent, a pooling of resources is necessary. This pooling, in the instant case, involved a research study and a development of a computer program, which, after the initial cost of the study and the development of the computer program, allows each individual agency to obtain the cost data it so desperately needs for a relatively low cost. It appears that the approach taken in this article may also be relevant to the study about to be undertaken by the American Institute of Certified Public Accountants and would allow them to develop a workable program which could be implemented without disturbing the underlying accounting records of each voluntary agency for which adequate, uniform data is required.